Investor Sentiment and Stock Market Volatility: A Behavioral Finance Perspective - K. V. , Thomas; Santhosh Kumar, K (GS WOW: Wisdom of Worthy Research Journal, 2025)
This study examines the impact of Investor Sentiment, Risk Tolerance, Financial Literacy, Media Influence, Investment Experience, and Economic Expectations on Perceived Stock Market Volatility, with a focus on retail investors, financial professionals, and business owners in Kerala, India. Adopting a quantitative approach, data was collected from 100 respondents using a structured questionnaire. Statistical analysis, including correlation analysis and multiple regression modeling, was employed to assess the strength and significance of relationships among the variables. The reliability of constructs was verified using Cronbach’s Alpha, with all values exceeding 0.70, ensuring internal consistency. The regression analysis revealed that Investor Sentiment, Risk Tolerance, and Economic Expectations significantly influenced perceived stock market volatility, with an R-value of 0.781 and an Adjusted R-Square of 0.519, indicating that the selected factors explain a substantial portion of variations in perception. ANOVA results confirmed the model’s statistical significance (F = 13.79, p = 0.005). These findings highlight the crucial role of psychological and informational factors in shaping investor perceptions and emphasize the need for enhanced financial education, responsible media reporting, and strategic investment planning. The study provides insights that can aid policymakers, financial institutions, and investors in making informed decisions, ultimately contributing to a more stable and resilient investment environment.